Student Profile Toword Course Activities At PGSD FKIP University Widya Dharma Klaten - Bayu Purbha Sakti (JPDI (Jurnal Pendidikan Dasar Indonesia), 2019)
The research was backgrounded by a decrease in the number of students who enrolled in Unwidha Klaten's PGSD Study Program. The study focused on the profile of students towards the PGSD FKIP Klaten Widya Dharma University lecture activities. Data collection uses an instrument in the form of a questionnaire. Processing data using editing, explanation information, diagrams, and percentage explanations. The research conclusions are explained as follows. The majority of Unwidha Klaten's PGSD students in 2017 have self-explanations such as being born in Klaten before the millennium, having a productive age, having traits, and predominantly female characters. The majority of Unwidha Klaten's PGSD students in 2017 have family information such as having to struggle to get more information about bachelor diplomas, civil servants, private teachers, love their siblings, be an example, and a good example in the family. The majority of Unwidha Klaten's PGSD students in 2017 have health information such as being able to maintain their weight, height, eye health, hearing health, should not be considered arrogant because they do not have recurrence of disease and accident problems. The majority of Unwidha Klaten's PGSD students in 2017 have lecture information such as having the desire to become an elementary school teacher, taking a distance of more than 1 kilometer with up to 1 hour, choosing the subjects they like and the hardest courses, namely PGSD courses.